DOI: 10.11606/t.11.2020.tde-20200111-151027
|View full text |Cite
|
Sign up to set email alerts
|

Propriedades físico-hídrico-mecânicas de um latossolo roxo, sob diferentes sistemas de uso e manejo

Abstract: Ao Professor Dr. Paulo Leonel Libard� verdadeiro orientador em todas as etapas do curso, pela amizade e convívio. À Prefeitura Municipal de Guaíra-SP pelo apoio durante as atividades de campo, com a cessão da infra-estrutura do CEP AR, imprescindível para a realização deste trabalho. Ao Maurício Sakai, um dos proprietários da Fazenda Lagoa do Fogão, pela permissão de uso da área e por todo apoio sem os quais este trabalho não poderia ter sido realizado. Aos Professores Sérgio de Oliveira Moraes, Klaus Reichard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
0
4
0
4
Order By: Relevance
“…Water storage in the soil represents the water that the soil is storing in a specific layer in a specific depth. In figure 4 the results obtained by [33] are illustrated and determine the variation of water storage in the soil for three managements, between current humidity and PWP, for eight different redistribution times and five depths in determination experiment of function K(θ) by the instantaneous profile method. They concluded that until the 0,25 m layer, the under rainfed soil always retained more water than the woods soil and irrigated, having a higher variation between the woods and two other management systems.…”
Section: Depth (M) Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Water storage in the soil represents the water that the soil is storing in a specific layer in a specific depth. In figure 4 the results obtained by [33] are illustrated and determine the variation of water storage in the soil for three managements, between current humidity and PWP, for eight different redistribution times and five depths in determination experiment of function K(θ) by the instantaneous profile method. They concluded that until the 0,25 m layer, the under rainfed soil always retained more water than the woods soil and irrigated, having a higher variation between the woods and two other management systems.…”
Section: Depth (M) Managementmentioning
confidence: 99%
“…Variation of water storage in the soil for three managements, between the current humidity and PWP, for eight different drainage times and five depths[33] …”
mentioning
confidence: 99%
“…Five soil samples were collected at five different sites from each of the blocks, totaling 15 samples. An Uhland soil sampler with sterile stainless steel cylinders measuring 50 mm X 50 mm was used (Klein, 1998). Soil blocks were manually pressed out of the cylinders, and cut into 0.5-cm layers with a knife blade.…”
Section: Total and Fecal Coliform Counts In Soil Samples At Differentmentioning
confidence: 99%
“…After determining the layer that should be saturated, we calculated the amount of water to be added per m 2 (Libardi, 2005) using the soil water storage equation. These physical and hydro parameters allowed the calculation of the amount of disinfectant needed to saturate the dirt floor down to the desired depth (Klein, 1998), i.e., up to the point at which coliforms could be detected in the first phase of the study.…”
Section: Determination Of the Amount Of Disinfectant Needed To Saturamentioning
confidence: 99%
“…Essa fração da porosidade é então muito reativa com a solução no solo (porosidade residual); porém, esta água permanece retida com energia muito alta, sendo, portanto, indisponível às plantas. É a água que o solo retém quando o seu potencial mátrico se encontra abaixo do ponto de murcha permanente (< -1500 KPa) (KLEIN, 1998). O volume de água disponível para as plantas (água de retenção) localiza-se nos mesoporos que este autor define como estando na faixa de diâmetro entre 0,5 e 50 µm (porosidade de estoque).…”
Section: Revisão Bibliográficaunclassified